Análisis de la cartera de crédito vencida de la Cooperativa de Ahorro y Crédito San Antonio agencia Vinces en el periodo 2019-2020 - Solano Caregua, Sindy Yaritza (2021)
Cooperativa de Ahorro y Crédito "San Antonio" Ltda. Vinces Agency, is a private financial institution that is dedicated to offering its partners various financial products and services among them are consumer loans and microcredits, the administration of the credit portfolio lies in knowing how to analyze, study and evaluate the position or situation of the debtor and comply with the policies that the credit and collections department has to its advisors for the granting of credits to the respective partners, a problem would persist in the future if an adequate control over the ability to pay, or the economic situation and if the partners are not monitored or followed to see where the credit is going and whether or not they meet their destination; Failure to comply with these fundamentals causes a deficiency in credit management, generating an overdue portfolio due to default of payments, which induces financial instability in the cooperative.